A molecular dynamics simulation of the chemisorption of the optical isomers of propranolol on the graphitic electrode modified with melamine, cyanuric, and isocyanuric acids. Issue 3 (1st October 2018) - Ilyina, Margarita G.; Khamitov, Edward M.; Maistrenko, Valery N.
Abstract : To demonstrate the nature of the interaction of optical isomers of propranolol with the surface of the graphitic electrode modified with melamine, uracil, cyanuric, and isocyanuric acids, we have performed molecular dynamics simulations of the four‐component systems with variable modifier's molecules. We have considered the possible formation of complexes between the propranolol and modifier's molecules, covering the electrode approximated as the graphene surface. Our simulations demonstrate that thel ‐isomer in aqueous solutions is bonded to the electrode surface stronger than itsd ‐counterpart; hence, the difference in analytical signals arises. Different strengths of bonding of the propranolol enantiomers to the surface modifiers are caused by the different intramolecular interactions taking place in the molecules ofd ‐ andl ‐isomers. Thus, we have computationally shown that the modification of the graphite surface with melamine, uracil, cyanuric, and isocyanuric acids allows for increasing the sensitivity of the electrode toward the propranolol enantiomers and using the modified graphitic electrodes for the detection of itsd ‐ andl ‐forms. Abstract : To demonstrate the nature of the interaction of optical isomers of propranolol with the surface of the graphitic electrode modified with melamine, uracil, cyanuric, and isocyanuric acids, we have performed molecular dynamics simulations of the four‐component systems with variable modifier's molecules.